ChemInform Abstract: Synthesis of Functionalized N‐Triazolyl Maleimides. Issue 2 (January 2015) - Stefani, Helio A.; Ferreira, Fernando P.; Ali, Bakhat; Pimenta, Daniel C.
Abstract N‐Triazolyl maleimides (III) are prepared by copper catalyzed 1, 3‐cycloaddition of enantiopure N‐propargylpyrrole (I) with various azides.